IMPLEMENTATION OF ACTIVITY BASED COSTING OF LABORATORIUM AND RADIOLOGY UNIT IN INDONESIA: A LITERATURE STUDY - El Wahyuningsih; Henny A. Manafe; Hedwigh H. T. Lejap (SEAN Institute, 2023)
This literature study on the Application of the Activity Based Costing Method aims to examine the application and benefits of using the Activity Based Costing method in calculating laboratory inspection service rates. From the results of previous research, applying the Activity Base Costing method can produce more accurate cost information and can avoid cost distortions, so that it can help control operations, control costs and provide information for the hospital or clinic budget process. This research uses the method descriptive and literature review by identifying 8 articles that examine the application of the Activity Base Costing method in calculating laboratory and radiology examination service rates in the 2016 – 2023 range. The results show that the Activity Based Costing method can be applied to calculate the tariff for laboratory examination services and is able to increase accuracy, providing relevant cost information in setting rates for examination services in laboratories and radiology, can improve cost control and allocate indirect costs accurately, and identify activity costs properly and can increase operational efficiency in laboratory and radiology units. To apply the Activity Based Costing method , accuracy and precision are needed in identifying activities, accuracy and accuracy in determining the amount of drive costs and pool costs and requires sufficient time to be able to apply the Activity Based Costing method to obtain accurate results.